Water management and performance enhancement in a proton exchange membrane fuel cell system using optimized gas recirculation devices - Liu, Yang (2023)
Fuel gas utilization and water management are particularly challenging integrated engineering problems in hydrogen-oxygen proton exchange membrane fuel cell (PEMFC) systems. Ejectors are promising fuel cell exhaust gas recirculation devices that can be used to address both challenges. In this study, hydrogen and oxygen recirculation ejectors are designed and manufactured using three-dimensional (3D) printing technology. An experimental investigation on a 1 kW PEMFC system with anodic and cathodic dual-ejector- based gas recirculation is presented. Key parameters such as stack current, stack voltage, cell voltage, operating pressure, and mass flow rate at the primary flow and secondary flow of the anode ejector are measured. The performance of the PEMFC stack equipped with 3D-printed ejectors is compared to that of commercial ejectors. The experimental results reveal that the 3D-printed ejector significantly outperforms the commercial ejector in terms of entrainment ratio, with an improvement rate of up to 31.3%. The performance of the PEMFC stack in the dual-ejector recirculation mode increased by 4.75% with a current density of 320 mA cm−2 compared with dead ended mode in 130 kPa. Furthermore, the dual-ejector recirculation mode of the PEMFC stack outperforms that of the dead-end anode and cathode mode during dynamic loading by alleviating the gas shortage problem of the PEMFC stack.